2017
DOI: 10.3390/molecules22050847
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mitochondria Are Important for the Effect of Resveratrol

Abstract: Resveratrol (Resv) is a polyphenol reported to modulate mitochondrial activity. The aim was to use HeLa and 143B cells to characterize the action of Resv on mitochondrial activity, cell size and proliferation using wild type (WT) and Rho 0 cells deficient in mitochondrial DNA. In both HeLa WT and Rho 0 cells, the oxygen consumption rate (OCR) was increased at 20 µM Resv after 24 h, whereas only a non-significant increase of OCR was observed in 143B WT cells. Resv decreased cell number concentration-dependently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Resveratrol is believed to mimic the physiological effects of CR in a mainly SIRT1-or SIRT3-dependent manner [22,23]. Functional mitochondria have been reported to be important for the effects of RSV [24]. Thus, in the present study, this potential effect of RSV was evaluated in oxidative phosphorylation capacities and transcription factors involved in mitochondrial biogenesis in myoblasts of five patients harboring the m.3243A>G point mutation and five controls.…”
Section: Discussionmentioning
confidence: 97%
“…Resveratrol is believed to mimic the physiological effects of CR in a mainly SIRT1-or SIRT3-dependent manner [22,23]. Functional mitochondria have been reported to be important for the effects of RSV [24]. Thus, in the present study, this potential effect of RSV was evaluated in oxidative phosphorylation capacities and transcription factors involved in mitochondrial biogenesis in myoblasts of five patients harboring the m.3243A>G point mutation and five controls.…”
Section: Discussionmentioning
confidence: 97%
“…In non-alcoholic fatty liver disease (NAFLD), an upregulation of a fibrinogen is an independent risk factor of CVD. Studies with trans-resveratrol have shown that this polyphenol reduces the liver fat and hepatic enzymes such as glutamate pyruvic transaminase (SGPT) and gamma-glutamyl transpeptidase (g-GT), and it also ameliorates insulin resistance, thus preventing and reducing liver damage in NAFLD [34][35][36][37].…”
Section: Anti-oxidative Effects Of Fibrinogen/resveratrol Complexmentioning
confidence: 99%
“…This huge, diverse group of plant metabolites includes well-known compounds, such as the phytoalexin, resveratrol (3,4′,5-trihydroxy- trans -stilbene; RSV) and the flavonoid, quercetin [ 2 ]. The actions of RSV have been studied in several in vivo and in vitro approaches, demonstrating antioxidant, anti-inflammatory and anti-aging effects [ 3 ], but also pro-apoptotic anti-cancer properties [ 4 , 5 ] as well as antimicrobial activity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…By hosting the complexes of the respiration chain in their inner membranes (IMM), mitochondria are the predominant source for the cell’s most important energy carrier, adenosine triphosphate (ATP). Consequently, the control of mitochondrial activity is of utmost importance for cellular wellbeing [ 4 ] and, obviously also for the therapeutic action of RSV, as experiments in mitochondrial DNA deficient Rho 0 cells have revealed functional mitochondria to be crucial for the effects of RSV to occur [ 5 ]. Interestingly, experiments revealed a strong concentration-dependent impact of RSV on mitochondrial function, which is of major importance, due to the therapeutic potential of this polyphenol [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%